2013
DOI: 10.1111/ijfs.12362
|View full text |Cite
|
Sign up to set email alerts
|

Antilisterial effect of two bioprotective cultures in a model system of Iberian chorizo fermentation

Abstract: This study reports the different effects of two bioprotective cultures on the growth of different Listeria monocytogenes strains by a rapid assay simulating the first stage of Iberian chorizo fermentation. Ground pork with or without protective cultures was inoculated with L. monocytogenes and incubated under two different conditions simulating the traditional, slow fermentation temperature (7°C, 1 day) and a high, fast fermentation temperature (20°C, 1 day), followed in both cases by storage at 7°C for 13 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The aim of this study was to evaluate the effectiveness of a meat-borne strain, L. sakei CTC494, in comparison with in vitro-selected LAB strains isolated from cold-smoked salmon against L. monocytogenes that was artificially inoculated on different coldsmoked salmons, vacuum-packaged and stored at 8 °C for 21 days. L. sakei CTC494 is a recognized bacteriocinogenic (sakacin K) starter and bioprotective meat culture (Aymerich et al, 2000;Hugas et al, 1995;Hugas, 1998;Ortiz et al, 2014;Ravyts et al, 2008). Recently it has been assayed as a bioprotective culture in fresh-filleted fish (Costa et al, 2019).This challenge test strategy is intended to provide scientific information to the industry, supporting the implementation of biopreservation strategies aiming to minimize the growth and associated risk of L. monocytogenes in RTE fish products.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to evaluate the effectiveness of a meat-borne strain, L. sakei CTC494, in comparison with in vitro-selected LAB strains isolated from cold-smoked salmon against L. monocytogenes that was artificially inoculated on different coldsmoked salmons, vacuum-packaged and stored at 8 °C for 21 days. L. sakei CTC494 is a recognized bacteriocinogenic (sakacin K) starter and bioprotective meat culture (Aymerich et al, 2000;Hugas et al, 1995;Hugas, 1998;Ortiz et al, 2014;Ravyts et al, 2008). Recently it has been assayed as a bioprotective culture in fresh-filleted fish (Costa et al, 2019).This challenge test strategy is intended to provide scientific information to the industry, supporting the implementation of biopreservation strategies aiming to minimize the growth and associated risk of L. monocytogenes in RTE fish products.…”
Section: Introductionmentioning
confidence: 99%
“…Natural antimicrobials, such as nisin (which belongs to the class I bacteriocins), sakacins, pediocin PA-1, plantaricin BM-1, and leucocin A (which belong to the class II bacteriocins), can be used to control L. monocytogenes on RTE foods ( Ferreira and Lund, 1996 ; Nilsson et al, 1997 ; Franklin et al, 2004 ; Trinetta et al, 2010 ; Woraprayote et al, 2013 ; Ortiz et al, 2014 ; Balay et al, 2017 ; Xie et al, 2018 ). However, nisin is the only bacteriocin approved as a preserving additive in food.…”
Section: Listeria Monocytogenes and Stress Resistance Genesmentioning
confidence: 99%
“…sakei at a concentration of 6 log CFU/g did not provoke significant reduction in L. monocytogenes counts in a Portuguese dry-fermented sausage. However, Ortiz et al [ 115 ] showed that Ll. sakei , when added to meat batter in Iberian chorizo, showed an anti-listerial activity at either 7 or 20 °C, reducing by 2 log 10 units the pathogen counts.…”
Section: Application Of Selected Lab or Bacteriocins In Rte Dry-cured...mentioning
confidence: 99%
“…P. acidilactici produced a reduction of 3.3 log CFU/g L. monocytogenes counts after 8 days of sucuk fermentation at mild temperatures (22–24 °C). On the other hand, Ortiz et al [ 115 ] showed that a starter culture containing P. acidilactici in Iberian chorizo provoked an anti-listerial effect at 7 °C.…”
Section: Application Of Selected Lab or Bacteriocins In Rte Dry-cured...mentioning
confidence: 99%